LINGUOCULTUROLOGY AND THE REFLECTION OF CULTURAL VALUES IN RIDDLE DISCOURSE (Ideal Journal of Multidisciplinary Research, 2026)
This article examines the relationship between language and culture from the perspective of linguoculturology. The study discusses the theoretical foundations of linguoculturology, its main concepts, and its role in modern linguistics. Particular attention is given to riddles as a linguocultural phenomenon. Using examples from Uzbek and English riddles, the article analyzes how national culture, worldview, and collective experience are reflected through linguistic units. The research highlights the role of metaphors, symbolic images, and stereotypical representations in conveying hidden meanings in riddles. The findings show that riddles function not only as linguistic phenomena but also as carriers of cultural memory, national mentality, and traditional ways of understanding the world.
Keywords: linguoculturology, language and culture, riddles, national culture, linguocultural units, folklore